Resilience of Aspergillus westerdijkiae strains to interacting climate-related abiotic factors: effects on growth and ochratoxin A production on coffee-based medium and in stored coffee - Akbar, Asya; Medina, Angel; Magan, Naresh (MDPI, 2020)
We examined the resilience of strains of Aspergillus westerdijkiae in terms of growth and ochratoxin A (OTA) production in relation to: (a) two-way interacting climate-related abiotic factors of water activity (aw, 0.99–0.90) × temperature (25–37 °C) on green coffee and roasted coffee-based media; (b) three-way climate-related abiotic factors (temperature, 30 vs. 35 °C; water stress, 0.98–0.90 aw; CO2, 400 vs. 1000 ppm) on growth and OTA production on a 6% green coffee extract-based matrix; and (c) the effect of three-way climate-related abiotic factors on OTA production in stored green coffee beans. Four strains of A. westerdijkiae grew equally well on green or roasted coffee-based media with optimum 0.98 aw and 25–30 °C. Growth was significantly slower on roasted than green coffee-based media at 35 °C, regardless of aw level. Interestingly, on green coffee-based media OTA production was optimum at 0.98–0.95 aw and 30 °C. However, on roasted coffee-based media very little OTA was produced. Three-way climate-related abiotic factors were examined on two of these strains. These interacting factors significantly reduced growth of the A. westerdijkiae strains, especially at 35 °C × 1000 ppm CO2 and all aw levels when compared to 30 °C. At 35 °C × 1000 ppm CO2 there was some stimulation of OTA production by the two A. westerdijkiae strains, especially under water stress. In stored green coffee beans optimum OTA was produced at 0.95–0.97 aw/30 °C. In elevated CO2 and 35 °C, OTA production was stimulated at 0.95–0.90 aw.
Keywords: Aspergillus; ochratoxin A; climate change; growth; carbon dioxide; temperature; water stress